AN EVALUATION OF THE ISLAMIC STUDY IN THE FACULTY OF ECONOMICS : BASIS FOR CURRICULUM MODIFICATION - Siswanto , (Indonesian Management and Accounting Research, 2007)
The main problem of this study was to propose curriculum modifications for Islamic Study Program in a certain faculty of economics of a certain university in Jakarta. It also aimed to examine whether the existing Islamic Study is consistent with the vision and mission of the university, and has been arranged sequentially and logically, and fits the needs of the students. The study was designed as a descriptive, evaluative, development research. The study began with evaluating the data collected mostly through personal interviews, documentary analysis, results of workshops and questionnaires. Based on the results of evaluation that reflected the areas of curriculum modification, the study came up with certain recommendation on this Islamic Study Program. The modification is aimed to make the curriculum is consistent to the current trends of Economics Theory, Management Practices and Islamic Study, and supports the attainment of the vision and mission of the university as well as develops the further study on Islamic economics.JEL Classification:Key words: Islamic Study, Curriculum, CIPP (Context, Input, Process and Product) Model, Islamic Economic.